The Periphery of the Periphery - Klara Hrvatin (Asian Studies)
On the basis of individual East Asian objects from small Slovenian towns, which were not the subject of the collecting practices in Slovenia organised so far but were in the possession of individuals and used or held in a certain family, we will reconstruct a picture of the cultural and material connections between the Slovenian southwestern municipality Ilirska Bistrica and the East Asian region. We are particularly interested in who their owners were and what kind of East Asian objects they kept in their homes. Can we speak of “typical” East Asian objects in Slovenian households? The subject of this research will mainly be objects from the late 19th and the beginning of the 20th centuries, which coincides with the period when the most representative Slovenian collectors, such as Alma Karlin (1889‒1950), Ivan Skušek Jr. (1877‒1947) and Ivan John Jager (1871‒1959), gathered objects that today form the bulk of the East Asian collections in Slovenia.